There ain't no such Thing as a Free Lunch: Nachhaltigkeits- Zielkonflikte in der Hähnchenmast aus Verbraucherperspektive; There ain't no such Thing as a Free Lunch: Intra-sustainable Trade-offs in Broiler Production from a Consumer's Perception - Winnie Isabel Sonntag; Stefan Golze; Achim Spiller; Marie von Meyer-Hof̈er (German Journal of Agricultural Economics (GJAE), 2018)
Die Anforderungen der Gesellschaft an den Tierschutz in der Geflügelindustrie steigen. Die Forderungen sind allerdings aus produktionstechnischer Perspektive und aus Tier- und Umweltschutzsicht nicht immer konfliktfrei umzusetzen. Es ergeben sich Zielkonflikte auf unterschiedlichen Ebenen, wie bspw. zwischen Tierschutz, Klimaschutz und Wirtschaftlichkeit, aber auch zwischen verschiedenen Tierschutzdimensionen. Reaktionsmuster von Verbrauchern auf Zielkonflikte in der Hähnchenmast sind bisher nicht bekannt. Es wird deshalb anhand eines qualitativen Ansatzes untersucht, wie Verbraucher auf ausgewählte Zielkonflikte in der Hähnchenmast reagieren.(...) Die Ergebnisse zeigen, dass ein Bewusstsein der Verbraucher für Zielkonflikte in der Hähnchenmast kaum vorhanden ist. Die Entscheidungsfindung zur Lösung von Zielkonflikten war heterogen und insgesamt von Tierwohlpräferenzen dominiert. (Quelle: Verlag) – – Expectations of the society regarding the production of food, especially the production of broiler meat, are continuously rising. From a production-related and environmental protection point of view, consumer demands cannot be implemented without conflicts. Trade-offs are induced in different dimensions, for example between animal welfare, climate protection and profitability. Little is known about consumer re-action to trade-offs in broiler production. With the help of ten 90-minute half structured guideline-based interviews, which were supported by images, it was investigated if consumers were aware of the trade-offs in broiler production systems. During these interviews, participants were shown pictures of both, floor systems with litter and free-range housing. Afterward they were given short, neutral texts with information to help illustrating the trade-offs. The results show that consumer awareness regarding trade-offs in broiler production systems hardly exists. Furthermore, reactions of citizens when confronted with trade-offs were analyzed. The decision process to solve the trade-offs problems was heterogeneous and dominated by animal welfare preferences. In general, participants decision behavior was different between the positively framed (outdoor access) and the negatively framed (floor system with litter) system. Participants consideration regarding the negative system (floor system with litter) was very emotional in most cases. Furthermore, cognitive dissonances and suppression could be observed. In contrast, the pros and cons of the positively framed system (outdoor access) were evaluated more rational, with goal dominance for animal welfare arguments.
Keywords: 330